Brinjal hybrid Pusa Unnat – A hope for higher income for the farmers of Terai region of West Bengal - Saha, Partha; Tomar, B S; Munshi, A D; Behera, T K; Kumar, Ravinder; Lyngdoh, Y A; Rana, S C; Das, Sushen Kumar; Rahman, F H; Roy, Bikash; Sultana, Samima (Indian Horticulture, 2023)
Brinjal is one of the major vegetables grown in West Bengal. It can be cultivated throughout the year but its productivity depends on the variety and season. The major drawback is the non-availability of quality seeds of high yielding varieties and/or hybrids. In the Cooch Behar district of West Bengal, long black purple fruited varieties are mostly preferred both by farmers and consumers. Purba Bakla is a small village in Cooch Behar district of West Bengal under the Terai region and is very much suitable for growing brinjal crop.